Myanmar's ASEAN chairmanship : will it lead to national reconciliation - Coates, Eliane (2014)
Myanmar’s 2014 ASEAN Chairmanship will boost Naypyidaw’s courting of world opinion in favour of its reforms. However, Myanmar’s road to reform remains long and winding. ASEAN should nudge Naypyidaw towards greater national reconciliation.